2010
DOI: 10.1021/ac100961x
|View full text |Cite
|
Sign up to set email alerts
|

Binding Kinetics of Antiricin Single Domain Antibodies and Improved Detection Using a B Chain Specific Binder

Abstract: Single domain antibodies are the recombinantly expressed binding fragments derived from heavy chain antibodies found in camels and llamas. These unique binding elements offer many desirable properties such as their small size ( approximately 15 kDa) and thermal stability, which makes them attractive alternatives to conventional monoclonal antibodies. We created a phage display library from llamas immunized with ricin toxoid and selected a number of single domain antibodies. Phage selected on ricin were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 24 publications
5
70
0
Order By: Relevance
“…Finally, the V H Hs identified in this study may also prove useful in ricin toxin detection. Indeed, Anderson et al (36) developed a ricin-specific immunoassay using camelid V H Hs that can differentiate between ricin and the closely related protein RCA I. With this assay, they were able to achieve sensitive ricin detection (Ͻ100 pg/ml) using an anti-RTB V H H, B4, with an affinity for ricin of 2 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the V H Hs identified in this study may also prove useful in ricin toxin detection. Indeed, Anderson et al (36) developed a ricin-specific immunoassay using camelid V H Hs that can differentiate between ricin and the closely related protein RCA I. With this assay, they were able to achieve sensitive ricin detection (Ͻ100 pg/ml) using an anti-RTB V H H, B4, with an affinity for ricin of 2 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, antibodies that bind to different epitopes on either the A or B subunit are required for efficient detection of ricin. Anderson et al [22] reported on high affinity sdAbs against both RTA and RTB and their combined use in detection platforms that included sandwich ELISA and Luminex immunoassay. From the panel of six antibodies evaluated in this study, three epitopes, two from the B subunit and one for the A subunit, were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Pelat et al [20] has reported on the generation and characterization of phage library-derived human single-chain Fv (scFv) fragments with the capacity to neutralize biological activity of ricin. Similarly Anderson et al [21,22] and Walper et al [23] have generated and characterized phage-library derived single-domain antibodies (sdAbs) against RTA and RTB.…”
Section: Introductionmentioning
confidence: 99%
“…CD measurements were performed using a Jasco J-815 CD spectropolarimeter equipped with a PTC-423S peltier temperature control system, as described previously (Anderson et al, 2010).…”
Section: Melting Temperature By Circular Dichroismmentioning
confidence: 99%
“…Each variable domain has three CDRs, which have the greatest sequence variability and also form the antigen-binding pockets that determine the affinity and specificity of each antibody for its antigen (Muyldermans, 2001). In combination with phage display technology and biopanning, immune sdAb libraries containing high affinity binder repertoire provide a facile route to select highly specific and strong affinity antibodies for sensitive detection of bio-threat agents (Anderson et al, 2010;Conway et al, 2010;Graef et al, 2011;Sherwood et al, 2007;Walper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%